Um psiquismo materno também portador de necessidades especiais? - Cynthia da Conceicao Tannure (2006)
This paper discusses the psychical burden on the mother who gives birth to a mentally defective child. In order to fully grasp the significance of motherhood in the life of a woman, we carried out a brief overview of the history of maternal love in light of the psychoanalytical theories developed by Freud and Melanie Klein. We investigated the nature of the narcissistic and traumatic impact experienced by the mother when the child that is born fails to live up to her expectations and desires. Finally, in view of our clinical experience, we highlighted four representations that a mentally defective child can assume in the mother's psyche as well as the defense mechanisms it triggers. From these considerations we concluded that the mother's psyche in distressful situations, as described above, is also in need of attention.